Representações da natureza da luz para descrição do seu comportamento - Rodrigues, Gustavo da Silva (Universidade Federal de São Carlos, 2025)
One of the most fundamental and earliest principles of quantum mechanics is wave-particle duality. This concept establishes that light can behave as either a wave or a particle, depending on the conditions of the experiment. Likewise, subatomic particles, such as electrons, exhibit characteristics of both particles and waves, challenging classical conceptions about the nature of matter and radiation. The study of the nature of light has been a central theme in physics since ancient times, motivating debates and scientific advances throughout history. In this work, we theoretically presented the corpuscular and wave representations to describe the nature and behavior of light and how they have evolved over time. The methodology adopted includes the definition of the concepts of wave and particle, the historical contextualization of each theory, the presentation of the fundamental principles, the deduction of the associated mathematical formulas, the limitations of each approach, and an explanation of what is the wave-particle duality. Through a literature review, we aim to present an understanding of the way in which the behavior of light is approached in physics education, in order to foster a deeper comprehension of the related physical concepts and their technological applications. Furthermore, we discussed suggestions for including the duality of light subjects in the basic education curriculum, aiming at better preparing students for the challenges of contemporary scientific knowledge.
Representations of the nature of light to describe its behavior
Keywords: Dualidade Onda-Partícula; Mecânica Quântica; Comportamento da Luz; Ensino de Física; Teorias da Luz; Wave-Particle Duality; Quantum Mechanics; Behavior of Light; Physics Teaching; Theories of Light; CIENCIAS EXATAS E DA TERRA::FISICA